A RASSF1A polymorphism restricts p53/p73 activation and associates with poor survival and accelerated age of onset of soft tissue sarcoma - Yee, Karen S. (Cancer Res, 2012)
RASSF1A (Ras association domain containing family 1A), a tumor suppressor gene that is frequently inactivated in human cancers, is phosphorylated by Ataxia Telangiectasia Mutated (ATM) on Ser131 upon DNA damage, leading to activation of a p73-dependent apoptotic response. A single nucleotide polymorphism located in the region of the key ATM activation site of RASSF1A predicts the conversion of alanine (encoded by the major G-allele) to serine (encoded by the minor T-allele) at residue 133 of RASSF1A (p.Ala133Ser). Secondary protein structure prediction studies suggest that an alpha helix containing the ATM recognition site is disrupted in the serine isoform of RASSF1A (RASSF1A-p.133Ser). In this study, we observed a reduced ability of ATM to recruit and phosphorylate RASSF1A-p.133Ser upon DNA damage. RASSF1A-p.133Ser failed to activate the MST2/LATS pathway, which is required for YAP/p73 mediated apoptosis, and negatively affected the activation of p53, culminating in a defective cellular response to DNA damage. Consistent with a defective p53 response, we found that male soft tissue sarcoma patients carrying the minor T-allele encoding RASSF1A-p.133Ser exhibited poorer tumor-specific survival and earlier age of onset compared with patients homozygous for the major G-allele. Our findings propose a model that suggests a certain subset of the population have inherently weaker p73/p53 activation due to inefficient signaling through RASSF1A, which affects both cancer incidence and survival.